2016
DOI: 10.1111/ajad.12366
|View full text |Cite
|
Sign up to set email alerts
|

An independent replication of the Adolescent‐Community Reinforcement Approach with justice‐involved youth

Abstract: Background and Objectives Substance use disorders among youth remain a serious public health problem. Although research has overwhelmingly supported the use of evidenced-based interventions, one of the primary limitations of the current evidence base is that for the vast majority of treatments, the developers of the treatments are also the ones conducting research on them, raising the possibility of allegiance bias. Methods The present study was an independently conducted randomized controlled trial (n =126)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Originally developed as the Community Reinforcement Approach (CRA), it was tested successfully with adults (Azrin et al, 1982; Hunt and Azrin, 1973) and then adapted for application with adolescents and clinically validated in several randomized trials with this age group (Dennis et al, 2004a; Godley et al, 2007, 2014; Henderson et al, 2016; Slesnick et al, 2007). A-CRA is predicated on helping clients better engage in their community.…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally developed as the Community Reinforcement Approach (CRA), it was tested successfully with adults (Azrin et al, 1982; Hunt and Azrin, 1973) and then adapted for application with adolescents and clinically validated in several randomized trials with this age group (Dennis et al, 2004a; Godley et al, 2007, 2014; Henderson et al, 2016; Slesnick et al, 2007). A-CRA is predicated on helping clients better engage in their community.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Additionally, there are sessions designed for parents/caregivers and joint family sessions for the adolescent and parent/caregiver. Prior research has shown that A-CRA has relatively high and equivalent rates of treatment initiation, engagement, retention, and participant satisfaction across gender and ethnic groups (Godley et al, 2011b), co-occuring substance and mental health disorders, and juvenile justice problems (Godley et al, 2014; Henderson et al, 2016). Although CRA in combination with methadone or naltrexone has been successfully tested in studies with adults (Abbott, 2009; DeJong et al, 2007), there are no published studies of A-CRA for opioid problems with or without medication assistance and some researchers have called for the need to do so (Clemmey et al, 2004).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Specifically, this model focuses on increasing prorecovery peers and activities in the community to compete with, reduce, and eventually replace substance use with constructive prosocial activities that support the development of recovery capital (Best et al, 2012;Cloud & Granfield, 2008;McKay, 2017). Research on A-CRA has demonstrated that it is effective as primary treatment for youth with substance use problems (Henderson et al, 2016;Hogue, Henderson, Becker, & Knight, 2018) and as continuing care recovery support following residential services (Garner, Godley, Funk, Lee, & Garnick, 2010;Godley et al, 2007Godley et al, , 2014.…”
Section: The Vrsa Modelmentioning
confidence: 99%
“…In a different trial, Henderson et al 72 compared three months of outpatient A-CRA followed by three months of ACC to services as usual provided by a juvenile probation department. One hundred twenty-six youth between 12–17 years old were enrolled in the study.…”
Section: Research On Continuing Care For Adolescents After Outpatientmentioning
confidence: 99%